Analysis of heavy metals in sludge from industrial wastewater treatment plant - Reena Sabrina, binti Yusuf Latif. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The presence of heavy metals in the sludge produced in wastewater treatment plant restricts plants growth hence their use for agricultural purposes. Studies have shown that the sludge is suitable for land application since it rich in nutrients. The aim of this study was detennine the levels ofpotential toxic elements namely Fe, Cu, Mn, Cr, Pb and Zn in the raw sludge samples from industrial wastewater treatment plants ofTex Cycle by employing Flame Atomic Absorption Spectroscopy (F AAS). In addition, the sludge samples also have been characterized for pH, organic matter and particle size distributions and also analyzed for their nutrient contents (N and P). The highest element present in the sludge samples was Fe and the least abundant element was Mn. The levels of heavy metals content in the sludge did not exceed the limits designated by Environmental Protection Agency United State and European Legislation. The sludge is suitable to be applied as soil amendment and also can be used as fertilizers since it has high organic matter content and rich in nutrients (N and P).